The binding properties of some novel ruthenium (III) complexes with human serum transferrin - Uivarosi, V.; Mitrea, N.; Dragoi, C.M.; Nicolae, A.; Arsene, A.L. (Вiopolymers and Cell, 2011)
Aim. The transferrin cycle gained increased interest in recent years and it holds promise as an attractive system for strategies of drug targeting to tumors. Neoplasic cells exhibit a large demand of iron and therefore express highly transferrin receptors. As a consequence, transferrin conjugates can preferentially interact with cancer cells. This strategy is exploited nowadays for targeting novel anti-cancer drugs. Recent data showed that ruthenium (III) compounds possess antitumor and antimetastatic effects, due to their affinity for crucial biomolecules (like transferrin). Methods. The paper presents the transferrin-binding properties of some novel ruthenium (III) complexes with general formula RuL2 (DMSO) mCl3 ·nH2O ((Ru-nf) L: norfloxacin (nf), m = 1, n = 1; (Ru-cpx) L: ciprofloxacin (cpx), m = 2, n = 2; (Ru-oflo) L: ofloxacin (oflo), m = 1, n = 1; (Ru-levo) L: levofloxacin (Levo), m = 2, n = 8; (Ru-pip) L: pipemidic acid (pip), m = 1, n = 2, DMSO: dimethylsulfoxide). We investigated, in vitro, the interactions of these ligands with human transferrin through spectroscopic techniques, with the ultimate goal of preparing adducts with good selectivity for cancer cells. Results. All studied complexes interact with human serum transferrin; the molar ratio [complex]/[transferrin] strongly influences the binding affinity. Conclusions. The best interaction between the complexes studied and transferrin is achieved for a molar ratio of 8; the best interaction was registered for Ru-pip, followed by Ru-nf. Keywords: ruthenium (III) complexes, transferrin. Мета. Останніми роками трансфериновий цикл викликає по - силений інтерес як перспективна система цільової доставки протипухлинних препаратів безпосередньо в пухлину. Неопластичні клітини потребують багато заліза, через що експресують велику кількість трансферинових рецепторів. Внаслідок цього кон ’югати трансферину здатні насамперед взаємодіяти з раковими клітинами. Цю стратегію у наш час використовують для пошуку нових протиракових препаратів. Останні дані демонструють, що сполукам рутенію (III) притаманні протипухлинні і антиметастатичні ефекти завдяки їхній афінності до важливих біомолекул (таких як трансферин). Методи. У статті представлено трансферин-зв’язувальні властивості деяких нових комплексів рутенію (III) загальною формулою RuL2 (DMSO) mCl3 ×nH2O ((Ru-nf) L: норфлоксацин (nf), m = 1, n = = 1; (Ru-cpx) L: ципрофлоксацин (cpx), m = 2, n = 2; (Ru-of) L: офлоксацин (oflo), m = 1, n = 1; (Ru-levo) L: левофлоксацин (Levo), m = 2, n = 8; (Ru-pip) L: піпемідинова кислота (pip), m = = 1, n = 2, DMSO: диметилсульфоксид). Ми вивчали взаємодію in vitro цих лігандів з трансферином людини методом спектроскопії для одержання адуктів з високою селективністю до ракових клітин. Результати і висновки. Всі досліджувані комплекси взаємодіють з сироватковим трансферином людини, молярне співвідношення [комплекс]/[трансферин] значно впливає на зв’язувальні властивості. Найкращу взаємодію між аналізованими комплексами і трансферином відмічено при молярному співвідношенні 8:1, а також для Ru-pip і Ru-nf. Ключові слова: комплекси рутенію (III), трансферин. Цель. В последние годы трансферриновый цикл вызывает повышенный интерес как перспективная система целевой доставки противоопухолевых препаратов непосредственно в опухоль. Неопластические клетки испытывают высокую потребность в железе и, следовательно, экспрессируют много трансферриновых рецепторов. Вследствие этого конъюгаты трансферрина способны преимущественно взаимодействовать с раковыми клетками. Эту стратегию в настоящее время используют для поиска новых противораковых препаратов. Последние данные показывают, что соединения рутения (III) обладают противоопухолевым и антиметастатическим эффектами благодаря их аффинности к важным биомолекулам (таким как трансферрин). Методы. В статье представлены трансферрин-связывающие свойства некоторых новых комплексов рутения (III) с общей формулой RuL2 (DMSO) mCl3 ×nH2O ((Ru-nf) L: норфлоксацин (nf), m = 1, n = 1; (Ru-cpx) L: ципрофлоксацин (cpx), m = 2, n = 2; (Ru-of) L: офлоксацин (oflo), m = 1, n = 1; (Ru-levo) L: левофлоксацин (Levo), m = 2, n = 8; (Ru-pip) L: пипемидиновая кислота (pip), m = 1, n = 2, DMSO: диметилсульфоксид). Мы изучили взаимодействие in vitro этих лигандов с человеческим трансферрином методом спектроскопии для получения аддуктов, обладающих хорошей селективностью к раковым клеткам. Результаты и выводы. Все исследуемые комплексы взаимодействуют с человеческим сывороточным трансферрином, молярное соотношение [комплекс]/ [трансферрин] сильно влияет на связывающие свойства. Наилучшее взаимодействие между изучаемыми комплексами и трансферрином отмечено при молярном соотношении 8:1, а также для Ru-pip и Ru-nf. Ключевые слова: комплексы рутения (III), трансферрин.